Cellular components of the human medial amygdaloid nucleus. Issue 3 (17th December 2012) - Dall'Oglio, Aline; Xavier, Léder L.; Hilbig, Arlete; Ferme, Denise; Moreira, Jorge E.; Achaval, Matilde; Rasia‐Filho, Alberto A.
Abstract The medial nucleus (Me) is a superficial component of the amygdaloid complex. Here we assessed the density and morphology of the neurons and glial cells, the glial fibrillary acidic protein (GFAP) immunoreactivity, and the ultrastructure of the synaptic sites in the human Me. The optical fractionator method was applied. The Me presented an estimated mean neuronal density of 1.53 × 105 neurons/mm3 (greater in the left hemisphere), more glia (72% of all cells) than neurons, and a nonneuronal:neuronal ratio of 2.7. Golgi‐impregnated neurons had round or ovoid, fusiform, angular, and polygonal cell bodies (10–30 μm in diameter). The length of the dendrites varied, and pleomorphic spines were found in sparsely spiny or densely spiny cells (1.5–5.2 spines/dendritic μm). The axons in the Me neuropil were fine or coarsely beaded, and fibers showed simple or notably complex collateral terminations. The protoplasmic astrocytes were either isolated or formed small clusters and showed GFAP‐immunoreactive cell bodies and multiple branches. Furthermore, we identified both asymmetrical (with various small, clear, round, electron‐lucent vesicles and, occasionally, large, dense‐core vesicles) and symmetrical (with small, flattened vesicles) axodendritic contacts, also including multisynaptic spines. The astrocytes surround and may compose tripartite or tetrapartite synapses, the latter including the extracellular matrix between the pre‐ and the postsynaptic elements. Interestingly, the terminal axons exhibited a glomerular‐like structure with various asymmetrical contacts. These new morphological data on the cellular population and synaptic complexity of the human Me can contribute to our knowledge of its role in health and pathological conditions. J. Comp. Neurol. 521:589–611, 2013. © 2012 Wiley Periodicals, Inc.